STRATEGI PEMBELAJARAN AKTIF DI SEKOLAH DASAR - Rachmah, Huriah (MAJALAH ILMIAH WIDYA, 2012)
The active learning strategic is importand to implemented because mondays During the learning process is more often definedas a teacher explaining the material and the students listening whis is regarded as a passive interaction. The obbjective of this paperis to discuss the active learning, especially in primary schools with the aim to provide an overview and examples of applied learningin school as far as possible. The method used descriptive analysis . It is impotant to conclude that the strategy of active learning inschool will change even the reluctant learners become engaged learners and full appreciation. With active learning and carefulplanning, thoughtful teaching, the quality of learning will increase learners attention to follow the learning process as to to obtainparticipants â opportunities to ask questions, discuss, and actively using the new knowledge gained and it is easily understood and